Faktor -Faktor Yang Mempengaruhi Cakupan Imunisasi MR (Measles Rubella) di Wilayah Kerja Puskesmas Pekanbaru Kota Tahun 2025 - Yessi Rahayu; Ari Diansyah; Ardita Aldama; Fadila Rizki Yani (PPNI UNIMMAN, 2026)
Measles Rubella (MR) immunization coverage in Indonesia remains below the national target of 95%, with coverage in 2024 reaching only 82.3% and showing a decline compared to the previous year. A lower coverage was observed in the working area of Pekanbaru Kota Public Health Center, where only238 out of 547 eligible children (41.3%) received MR immunization. Low immunization coverage may reduce herd immunity and increase the risk of measles and rubella outbreaks. This study aimed to analyze factors influencing MR immunization uptake among children under five in the working area of Pekanbaru Kota Public Health Center in 2025. This quantitative study employed a cross-sectional design involving 40 mothers of children aged 9–60 months selected through accidental sampling. Data were collected using structured questionnaires assessing maternal knowledge, attitudes, family support, support from health workers, and travel time to health facilities. Univariate and bivariate analyses were performed using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that 67.5% of respondents had provided MR immunization to their children. Significant associations were found between maternal knowledge (p = 0.033), maternal attitudes (p = 0.037), family support (p = 0.002), and health worker support (p = 0.015) with MR immunization uptake, while travel time to health facilities was not significantly associated (p = 0.053). In conclusion, maternal knowledge and attitudes, family support, and health worker support are significant factors influencing MR immunization uptake, highlighting the need to strengthen health education and family involvement to improve MR immunization coverage.